Visual and auditory event related potentials in epileptic children: a comparison with normal and abnormal MRI findings - TÜRKDOĞAN, DİLŞAD; AKYÜZ, GÜLSEREN DERYA (My University, 2003)
Visual and auditory event related potentials (VERPs and AERPs) in 32 epileptic children with magnetic resonance imaging (MRI) abnormalities and 18 with normal MRI were recorded and compared to the data of 21 healthy children. Of all 50 epileptic children (34 male, 16 female) aged 14.42+/-4.27 (7-20) years, 21 were medically intractable and receiving polytherapy. The mean latencies of N2 and P3 components of VERPs and AERPs in all epileptic children were significantly higher than those of the controls (P<0.05). Epileptic children with structural abnormalities had more prolonged latencies of N2 and P3 components of AERPs and VERPs than those of the healthy children (P<0.05). The epileptic children with normal MRI had significantly more prolonged latency of N2 and P3 of VERPs and P3 of AERPs than those of the controls (P<0.05). The difference of the mean latency of N2 and P3 components or the mean amplitude of P3 components of ERPs between the two epileptic groups was insignificant. The type of medication (mono- versus polytherapy) did not affect the wave components of ERPs. We suggest that epileptic activity, itself, leads to prolonged N2 and P3 components of AERPs and VERPs. The presence of structural abnormality indicated by imaging is not a predictor of ERPs abnormalities.
Keywords: Adult; Female; Humans; Adolescent; Male; Child; Brain; Magnetic Resonance Imaging; Radiography; Event-Related Potentials, P300; Evoked Potentials, Auditory; Epilepsy; Evoked Potentials, Visual